The Use of the Cognitive Behavioral Therapy for the Treatment of Migraine and Tension Type Headaches - Yasemin Akkoca; Þehnaz Yýldýrým; Levent Ertuðrul Ýnan (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Headache, which affects a large part of the community and causes loss of workforce, is gaining importance in terms of the burden which it brings on the society, by its function of restricting individuals social activities as well as increasing the health expenditure likewise drug consumption. Migraine and tension headaches are primary headaches which any organic causes can not be determined for them. For the treatment of headaches of this type besides the use of medicine, exercises with bio-feedbacks and acupuncture; in recent years cognitive behavioral treatments (CBT) appears to be effective. It’s shown that the negative mode of thinking onindividuals which have recurrent headaches, stimulates the headache, increase its severity and complicates the management of it. CBT provides for the person a self-help opportunity even the therapy is terminated, besides behavioral methods such as relaxation exercises, by developing strategies of self-monitoring, education, abilities of pain management and coping with the maladaptive beliefs and houghts. The purpose of this text is, providing information about the use of the cognitive behavioral therapies on primary headaches and basic principles of treatment. [JCBPR 2015; 4(1.000): 10-17]